Using ostraca in the ancient world: new discoveries and methodologies - Caputo, Clementina; Lougovaya-Ast, Julia; Bülow-Jacobsen, Adam; Haring, Ben J. J.; Redon, Bérangère; Cromwell, Jennifer; Schentuleit, Maren; Folmer, Margaretha; Chaufray, Marie-Pierre; Davoli, Paola; Lippert, Sandra L. (Materiale Textkulturen, 2020)
Klappentext: Throughout Egypt’s long history, pottery sherds and flakes of limestone were commonly used for drawings and short-form texts in a number of languages. These objects are conventionally called ostraca, and thousands of them have been and continue to be discovered. This volume highlights some of the methodologies that have been developed for analyzing the archaeological contexts, material aspects, and textual peculiarities of ostraca.
Keywords: Konferenzschrift; Geschichte; Ostrakon; Griechenland; Ägypten